Associations between schizotypal personality features, mentalizing difficulties and thought problems in a sample of community adolescents. Issue 3 (23rd June 2020) - Salaminios, George; Morosan, Larisa; Toffel, Elodie; Tanzer, Michal; Eliez, Stephan; Badoud, Deborah; Armando, Marco; Debbané, Martin
Abstract: Aim: Schizotypal trait expression and mentalizing impairments represent key factors associated with increased vulnerability for schizophrenia. In the current study, we analysed the nature of associations linking specific schizotypal personality features to mentalizing difficulties during adolescence. Furthermore, we examined the extent to which mentalizing difficulties mediate the relationship between schizotypal trait features and self‐reported thought problems. Methods: One hundred and five community adolescents ( M age = 15.72; SD = 1.91) completed a recently developed self‐report measure of mentalizing (Reflective Functioning Questionnaire [RFQ]), evaluating the degree of certainty (RFQc‐scale) and uncertainty (RFQu‐scale) with which individuals utilize mental state information to understand their own and others' behaviour. High scores on the RFQu‐scale reflect poor usage of mental state information, while high scores on the RFQc‐scale capture adaptive levels of certainty about mental states. Self‐report questionnaires were also used to assess schizotypal trait expression, thought problems and symptoms of anxiety/depression. Results: Linear regression models indicated that schizotypal features of social anxiety and odd speech accounted for increased RFQu scores, while odd speech also accounted for reduced RFQc scores. RFQu partially mediated the effects of social anxiety and odd speech on the level of thought problems in the sample. Conclusions: Present findings suggest that schizotypal features that impede interpersonal communication during adolescence are linked to difficulties in mental state understanding. Our study also provides original data suggesting that the effects of social anxiety and odd speech on psychosis‐risk may partially depend upon the level of mentalizing uncertainty. Mentalizing difficulties may constitute important clinical assessment and early prevention treatment targets in adolescents who demonstrate schizotypal features.